FULL TERM PREGNANCY WITH A HUGE RECURRENT IMMATURE TERATOMA: A CASE REPORT. - APHINIVES, Chalida; CHATYAKUM, Jitjaroen (The ASEAN Journal of Radiology, 2023)
Immature teratoma is an infrequent ovarian tumor in reproductive female, especially occurring with pregnancy. This report describes the radiologic findings in a 35- year-old woman, with 32-weeks pregnancy, presented a huge multiloculated cyst in the Cul-de-sac. Thirteen years ago, she was diagnosed to have an immature teratoma, but her treatment was not completed. At this time, cesarean section was performed when her pregnancy reached 36 weeks, but the biopsies of abdominal cysts revealed multicystic peritoneal mesothelioma. No further treatment was done because the patient refused to have.